Potential Benefits from Improved Energy Efficiency of Key Electrical Products: The Case of India - Michael McNeil, Maithili Iyer, Stephen Meyers, Virginie Letschert, James E. McMahon (2005)
The goal of this project was to estimate the net benefits that cost-effective improvements in energy efficiency can bring to developing countries. The study focused on four major electrical products in the world's second largest developing country, India. These products - refrigerators, room air conditioners, electric motors, and distribution transformers - are important targets for efficiency improvement in India and in other developing countries. India is an interesting subject of study because of it's size and rapid economic growth. Implementation of efficient technologies in India would save billions in energy costs, and avoid hundreds of megatons of greenhouse gas emissions. India also serves as an example of the kinds of improvement opportunities that could be pursued in other developing countries.